2004
DOI: 10.1193/1.1767161
|View full text |Cite
|
Sign up to set email alerts
|

Damage and Vulnerability Assessment of Churches after the 2002 Molise, Italy, Earthquake

Abstract: The 2002 Molise, Italy, earthquake sequence shocked the Italian public because it killed school children, but it also highlighted the fact that seismic vulnerability of historic masonry buildings has increased because of reinforcement work that has been done in the last 50 years. Replacing the original wooden roof structure with new reinforced concrete or steel elements, inserting reinforced concrete tie-beams in the masonry and new reinforced concrete floors, and using reinforced concrete jacketing on the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…Studies done on churches, starting from the observation of damage after the Friuli earthquake in 1976 (Doglioni et al 1994) and more systematically after the earthquakes in Umbria and the Marches in 1997 (Lagomarsino and Podestà 2004a) and Molise in 2002 (Lagomarsino and Podestà 2004c), have demonstrated that damage mechanisms in churches have certain recurring characteristics, notwithstanding the uniqueness of each site. In particular, the interpretation using macro elements has proven very useful, i.e.…”
Section: Seismic Vulnerability and Risk Prevention Of Cultural Heritagementioning
confidence: 97%
See 1 more Smart Citation
“…Studies done on churches, starting from the observation of damage after the Friuli earthquake in 1976 (Doglioni et al 1994) and more systematically after the earthquakes in Umbria and the Marches in 1997 (Lagomarsino and Podestà 2004a) and Molise in 2002 (Lagomarsino and Podestà 2004c), have demonstrated that damage mechanisms in churches have certain recurring characteristics, notwithstanding the uniqueness of each site. In particular, the interpretation using macro elements has proven very useful, i.e.…”
Section: Seismic Vulnerability and Risk Prevention Of Cultural Heritagementioning
confidence: 97%
“…In particular, the church form considers 28 damage and collapse mechanisms that can frequently occur in the different architectonic elements (named macroelements) which compose churches (Lagomarsino and Podestà 2004c). Table 1 shows the mechanisms considered and the related macroelement.…”
Section: The Damage Assessment Of Churches and Emergency Managementmentioning
confidence: 99%
“…By filling in all the other sections Downloaded by [George Washington University] at 04:26 08 February 2015 of the form, it is possible to register information about the church itself, general damage, and seismic vulnerability, and to assist decisions about the viability and detailing of temporary propping and other safety measures [Costa, 2009;Grimaz, 2011]. It is also possible to estimate the cost of the required structural interventions using an economic loss model, based on the damage level in each macroelement [Lagomarsino and Podestà, 2004b].…”
Section: Italian Survey Form For Churchesmentioning
confidence: 99%
“…According to Civil Protection Department [2006], inspectors are expected to identify possible collapse mechanisms from a list on the form and then grade the activated mechanisms within a scale [Grunthal et al, 1998]: 1-Negligible to slight damage; 2-Moderate damage; 3-Substantial to heavy damage; 4-Very heavy damage; 5-Destruction. The first version of the form had 18 possible collapse mechanisms [Angeletti et al, 1997] and was used to assess almost 3,000 churches in Umbria-Marché, Italy, after the earthquake of September 26, 1997 [Lagomarsino and Podestà, 2004a] and in Molise, Italy, after the earthquake on October 31, 2002 [Lagomarsino and Podestà, 2004b]. The form was also applied in the Azores, Portugal, after the earthquake on July 9, 1998 [Guerreiro et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The experience in seismic areas showed that this type of buildings is subjected to typical and repetitive damage mechanisms (Doglioni [5], Lagomarsino [6]), as: the façade overturning, the in plane damage of the lateral walls, the damage of the apse and of the bell tower, etc.…”
Section: Introductionmentioning
confidence: 99%